2015
DOI: 10.1007/s11113-015-9368-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Maternal Postpartum Depression: The Importance of Stress Type and Timing

Abstract: Interest in identifying social risk factors for maternal postpartum depression has increased, with a growing emphasis placed on stress exposure. Despite increased interest, questions about the importance of lifetime stress exposure relative to stress surrounding childbirth, along with the importance of different types of stressful events, remain unanswered. The stress process model has gained prominence as a guiding framework for examining stress type and timing in studies of major depression and poor pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…These findings are consistent with those from previous studies that reported increased risk of postpartum depressive symptoms in women with preterm birth [ 5 , 7 9 ]. Although, no study has previously examined the effect of successive preterm birth on the risk of postpartum depressive symptoms, Bener reported that postpartum mothers of preterm infants with a history of preterm birth had higher prevalence of psychological distress [ 32 ], which may increase their risk of developing postpartum depressive symptoms [ 12 ]. The elevated risk of postpartum depressive symptoms observed in women with preterm birth in the current study may be due to an increase in maternal level of stress associated with infant illness and complications and concerns about the infant's outcome as explained by the preterm parental distress model [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with those from previous studies that reported increased risk of postpartum depressive symptoms in women with preterm birth [ 5 , 7 9 ]. Although, no study has previously examined the effect of successive preterm birth on the risk of postpartum depressive symptoms, Bener reported that postpartum mothers of preterm infants with a history of preterm birth had higher prevalence of psychological distress [ 32 ], which may increase their risk of developing postpartum depressive symptoms [ 12 ]. The elevated risk of postpartum depressive symptoms observed in women with preterm birth in the current study may be due to an increase in maternal level of stress associated with infant illness and complications and concerns about the infant's outcome as explained by the preterm parental distress model [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that even though preterm birth in the index delivery increases the risk of postpartum depressive symptoms, the risk may only be evident in women with very preterm birth. This may be due to greater level of stress in women with very preterm birth [ 33 ], as higher maternal stress levels have been associated with greater postpartum depressive symptoms [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study involving developed and Sub-Saharan African countries revealed that the experiences of stressful life events during pregnancy and in the postpartum period were significant predictors of PPD especially among women with a history of mental health problems [29] [30] [31]. A study by [32] using in-person interviews of 4362 women and data from medical records showed that any experience of stress (acute and chronic) is significantly associated with PPD and that acute stressors occurring before pregnancy and during birth have long-lasting effects on maternal mental health.…”
Section: Stress and Ppdmentioning
confidence: 99%
“…The majority of primiparous woman signs of anxiety are often overlooked due to a lack of awareness of the impact of later life on the child's mother, husband or other family relationships which will be a psychological burden for primiparaous. In addition, the ignorance and shame that is possessed to express the form of anxiety that is being experienced due to environmental stigma regarding psychological complaints becomes the cause of the post-partum process maladptation that cannot be overcome early on (Reid, 2015 ).…”
Section: Introductionmentioning
confidence: 99%